On the optimization of energy systems: Results utilization in the design process - Ganjehkaviri, A. (Elsevier Ltd., 2016)
This paper proposes a new methodology to provide a flexible optimum design tool for the multi-objective optimization of energy systems. There are many articles published on the optimization of energy systems, which use a multi-objective evolutionary algorithm for different cases. However a general method for optimization results utilization in design process is not presented to the authors’ knowledge and usually equilibrium point concept is used to select the optimal solution. Here a new method is proposed to improve the optimization results utilization in the design process. This method is applied on a simple energy system to consider the correlations between the design parameter and objective functions. The proposed method is flexible and easy to implement in any design problem. Results provide a neat process of optimum design includes cost limited maximum efficiency and components parameters selection like the condenser pressure and sub cool and superheat degrees. Results also show that compressor efficiency is the most powerful parameter in the case, which has the most significance effects on the optimization results.